Cultural Dynamics: Omugorogoro And The ‘Culturalization’ Of Hunger Among The Abaluhyia Of Western Kenya - Wandere, Donald Oluchina (Advances in Social Sciences Research Journal, 2019)
Issues on the interconnections between culture and hunger in general, and the influences the latter impacts on the former in particular, are largely ignored among scholars. When socio-cultural variables relative to hunger are taken as analytical tools, they are more often considered in terms of their independent rather than their dependent value. The reason for this approach is understandable; that the debilitating threat hunger poses on mankind is so urgent and critical, particularly in terms of human morbidity and mortality that it has to be approached in an applied sense, that is, as a phenomenon that warrants a pragmatic approach. This is a preferred mode to that which sees the problem (hunger) as one which may impact on the otherwise ’’inert’’, and ’’inconsequential’’ human social and cultural behaviour and the institutions therein. This paper discusses the concept of omugorogoro, a figurative term configured and socially institutionalized representation of hunger among the Abaluyia nation of Western Kenya. As a linguistic embodiment categorizing a food deficit situation, the paper argues that the institutionalization of omugorogoro depicts some form of social situation – indeed, a ‘lifestyle’ among a large cross-section of the rural Abaluyia populace of Western Kenya. Seen in this perspective, hunger assumes a life of its own - as an aspect of the culture of the Abaluyia, and with appropriate behavioural accompaniments. The discussions in this paper are mainly based on a study done among the Banyore sub-tribe of Abaluyia, and whose findings are documented in Wandere [13].